Seismic behavior of ductile rectangular composite bridge piers. - Chen, S. J. (Earthquake engineering & structural dynamics.)
The seismic resistance characteristics of a newly developed composite bridge pier system are examined via a series of experimental studies. In this innovative bridge pier system, the shear strength is provided by the steel tube and the concrete confined by the steel tube. No transverse shear reinforcement is used in this system. Axial and flexural strengths of the bridge pier are exerted by the longitudinal reinforcements and the concrete. A gap between the end of steel tube and the reinforced concrete foundation contributes to the steel tube providing shear resistance only without sharing the flexural moment. From the experimental results of this study, it is found that the flexural strength of the proposed composite bridge pier can be predicted accurately by the conventional method that was used in the reinforced concrete structures. Shear strength of the composite bridge pier can be obtained by summing up shear strengths of the concrete and the steel tube. Excellent deformation capacities are also found from the experimental studies. The proposed composite bridge pier system not only simplifies the construction work greatly, but also provides superior seismic resistance as compared with that of the conventional method.